The reception and transmission of Boethius's De Consolatione Philosophiae in late medieval England - Peak, K (2024)
This study advances our understanding of how Boethius’s De Consolatione Philosophiae was read in England in the fourteenth and fifteenth centuries. The reception of the Consolatio does not conform to easy categorisation; it was a popular text in the Middle Ages, equally at home in secular and religious contexts. It could sit happily with Boethius’s other works which formed part of the university quadrivium but also lent itself to literary interpretation and reinvention. It is therefore useful to study the work’s material transmission, to gain a wider perspective of the nature of reception and transmission of texts in fourteenth- and fifteenth-century England.